Development of a novel measure of advanced cancer patients' perceived utility of secondary germline findings from tumor genomic profiling - Jada G. Hamilton; Ibrahim H. Shah; Caroline Salafia; Elizabeth Schofield; Margaux Genoff Garzon; Kechna Cadet; Zsofia K. Stadler; Jennifer L. Hay; Kenneth Offit; Mark E. Robson (Elsevier, 2023)
Objective: Tumor genomic profiling (TGP) can inform advanced cancer patients' treatment decisions, and also reveal secondary germline findings-information about inherited risks for cancer and other disorders. We sought to develop a measure of patient perceptions of the clinical and personal utility of secondary germline findings. Methods: We developed a draft survey based on literature and patient interview data (n=40). We evaluated and refined the survey through cognitive interviews with advanced cancer patients who received secondary germline findings from TGP (n=10). The survey was psychometrically validated with data from two independent samples of advanced cancer patients undergoing TGP (total n=349). Results: Cognitive interviews offered opportunities for survey refinement and confirmation of its comprehensible nature. Exploratory and confirmatory factor analysis of the survey identified 16 items across three subscales with strong internal consistency (Cronbach's alpha ≥0.79): perceived utility for others, perceived utility for self and health, and confidence in secondary findings. Conclusion: We developed a novel valid scale with promise for measuring advanced cancer patients' perceptions of the utility of secondary germline findings. Innovation: We offer a new patient-derived measure of perceived utility of and confidence in secondary germline findings with potential applications for precision oncology research and clinical communication.